2019
DOI: 10.1109/tgcn.2019.2916325
|View full text |Cite
|
Sign up to set email alerts
|

New Power Minimization Techniques in Hybrid Distributed Antenna Systems With Orthogonal and Non-Orthogonal Multiple Access

Abstract: Distributed antenna systems have been proposed as a solution to supply the ever increasing capacity demands in next generation networks. This paper considers the power minimization problem in hybrid distributed antenna systems where antennas are supplied by various-low power and high power-energy sources. Antenna-specific power limits are considered and the problem is reformulated in this new hybrid context. The optimal power allocation problem is first formulated and solved in the orthogonal multiplexing scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In this paper, we study the combination of NOMA with HD-D2D and FD-D2D systems using mutual SIC. We introduced the concept of mutual SIC in our previous works [26][27][28] where we showed that the signals of two or more users multiplexed in NOMA, and powered by distributed antennas, can be decoded and removed at the level of every user in the NOMA cluster. In a D2D cellular scenario, this translates into removing the interference of the D2D devices at the level of the BS, and the interference of CU users at the level of D2D pairs.…”
Section: B Contributionsmentioning
confidence: 99%
“…In this paper, we study the combination of NOMA with HD-D2D and FD-D2D systems using mutual SIC. We introduced the concept of mutual SIC in our previous works [26][27][28] where we showed that the signals of two or more users multiplexed in NOMA, and powered by distributed antennas, can be decoded and removed at the level of every user in the NOMA cluster. In a D2D cellular scenario, this translates into removing the interference of the D2D devices at the level of the BS, and the interference of CU users at the level of D2D pairs.…”
Section: B Contributionsmentioning
confidence: 99%
“…In [18] [19], resource allocation is studied in NOMA-DAS for the context of mixed-traffic users. In [14], subband and power allocation in NOMA-DAS was tackled for the minimization of the downlink cell power under fixed user rates, and the study was then adapted to incorporate hybrid RRH-specific power constraints in [20]. It was shown that, under specific SIC and PMC contraints, when the signals multiplexed on the same subband are sent from different RRHs, paired users can all cancel their respective interference, leading to the so-called "mutual SIC" (or "dual SIC" for the case of 2 users per subband).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, user-antenna association for non-CoMP users is based on the sole criterion of maximal RSS or channel gain. In a previous work, we studied the use of NOMA in a DAS network, and exploited the combination of NOMA with DAS to tackle the downlink power minimization problem under fixed user rates [25], and also under RRH-specific transmit power constraints [26]. We showed that, under some channel and transmit power conditions, when multiplexed signals are sent from different RRHs, paired users can both cancel the interference of each other, hence the name mutual SIC.…”
Section: Introductionmentioning
confidence: 99%